A better way: training for direct observations in healthcare. Issue 10 (19th August 2022) - Alfred, Myrtede; Del Gaizo, John; Kanji, Falisha; Lawton, Samuel; Caron, Ashley; Nemeth, Lynne S; Alekseyenko, A V; Shouhed, Daniel; Savage, Stephen; Anger, Jennifer T; Catchpole, Ken; Cohen, Tara
Abstract : Direct observation is valuable for identifying latent threats and elucidating system complexity in clinical environments. This approach facilitates prospective risk assessment and reveals workarounds, near-misses and recurrent safety problems difficult to diagnose retrospectively or via outcome data alone. As observers are an instrument of data collection, developing effective and comprehensive observer training is critical to ensuring the reliability of the data collection and reproducibility of the research. However, methodological rigour for ensuring these data collection properties remains a key challenge in direct observation research in healthcare. Although prior literature has offered key considerations for observational research in healthcare, operationalising these recommendations may pose a challenge and unless guidance is also provided on observer training. In this article, we offer guidelines for training non-clinical observers to conduct direct observations including conducting a training needs analysis, incorporating practice observations and evaluating observers and inter-rater reliability. The operationalisation of these guidelines is described in the context of a 5-year multisite observational study investigating technology integration in the operating room. We also discuss novel tools developed during the course our project to support data collection and examine inter-rater reliability among observers in direct observation studies.